Congress and the Cold War - Johnson, Robert David, 1967- (New York : Cambridge University Press, 2006)
"This book provides the first historical interpretation of the congressional response to the entire Cold War. Using a wide variety of sources, including several manuscript collections opened specifically for this study, the book challenges the popular and scholarly image of a weak Cold War Congress, in which the unbalanced relationship between the legislative and executive branches culminated in the escalation of the U.S. commitment in Vietnam, which in turn paved the way for a congressional resurgence best symbolized by the passage of the War Powers Act in 1973"--Jacket
Constructing a bipartisan foreign policy -- Legislative power and the Congressional right -- Redefining Congressional power -- The consequences of Vietnam -- The transformation of Stuart Symington -- The new internationalists' Congress -- The triumph of the Armed Services Committee.
Includes bibliographical references and index.
Print version record.
English.
eBooks on EBSCOhost
Keywords: United States. -- Congress -- History -- 20th century; États-Unis. -- Congress -- Histoire -- 20e siècle.; United States. -- Congress; USA -- Congress; United States -- Foreign relations -- 1945-1989.; Cold War; Legislative oversight -- United States -- History -- 20th century; Guerre froide; Contrôle parlementaire -- États-Unis -- Histoire -- 20e siècle.; États-Unis -- Relations extérieures -- 1945-1989.; POLITICAL SCIENCE -- Government -- International; POLITICAL SCIENCE -- International Relations -- General; Diplomatic relations; Legislative oversight; United States; Ost-West-Konflikt; Außenpolitik; 1900-1999; History